A SECURE DIGITAL TRADING PLATFORM FOR ONLINE GAME ACCOUNTS USING DUAL AUTHENTICATION AND SMART PAYMENT INTEGRATION - Lalu Moh. Nurkholis; San Sudirman; Maspaeni; Muhammad Said (Ninety Media Publisher, 2026)
The rapid growth of online gaming has increased the economic value of game accounts, leading to the emergence of online game account trading. However, most transactions are still conducted through informal channels, such as social media and online forums, which lack security, transparency, and reliable transaction records. This study aims to design and implement a web-based information system for online game account buying and selling by integrating OTP-based dual authentication and a payment gateway to improve security and transaction efficiency. The system was developed using the Waterfall method, consisting of requirement analysis, system design, implementation, testing, and maintenance stages. UML diagrams and an Entity Relationship Diagram were used to model system functionality and database structure. The system was implemented using PHP and MySQL and supports key features such as user management, game account management, secure login with OTP, transaction processing, payment gateway integration, reviews, and complaints. Black-box testing results indicate that all system functions operate according to the defined requirements. The implementation of OTP-based authentication improves access security by reducing the risk of unauthorized account use, while payment gateway integration ensures accurate and automated payment verification. The system also enhances transaction transparency through digital transaction records and purchase history. The results show that the proposed system provides a secure, efficient, and practical solution for online game account trading in a local business environment, supporting digital transformation and service professionalism for small-scale enterprises.